Plain abdominal radiograph appearance in children with abdominal pain - Kemas Firman; Dora Darussalam; Rulina Suradi (Paediatrica Indonesiana, 2002)
Background Abdominal pain is a common condition in children. Plain abdominal radiograph is recommended routinely in the evaluation of children with abdominal pain.Methods A retrospective study was done to evaluate radiographic abnormalities in children with abdominal pain at the Department of Child Health Cipto Mangunkusumo Hospital from January 1, 1994 to December 31, 1998.Results Of the 76 patients with abdominal pain, there were 38 females and 38 males. Forty-five patients were in the >5-12 years age group. Thirty-five out of 76 patients showed radiographic abnormalities. The most common radiographic abnormality was stones (found in 13 patients), followed by uneven distribution of bowel air in 8 patients.Conclusion A plain abdominal radiograph is still required as a diagnostic tool for children with abdominal pain, especially in the acute stage.